Attendance at the Interparliamentary Conference on the CFSP/CSDP: Fostering the Emergence of a Parliamentary Epistemic Community in the EU?. (19th January 2021) - Schade, Daniel; Stavridis, Stelios
Abstract: There has been a gradual consolidation of interparliamentary cooperation over EU foreign and security policies (CFSP/CSDP). This has culminated in the setting up of a dedicated interparliamentary conference (IPC) on the CFSP/CSDP. This paper considers whether IPC gatherings in their current form help foster the creation of a transnational epistemic community of parliamentarians in foreign and security affairs and thereby aid the empowerment of parliamentary actors in the EU. To this end, IPC attendance patterns are analysed. The article finds that attendance at IPCs' diverges between EU parliaments. This and the fact that few parliamentarians choose to participate again reduces the IPC's utility to facilitate regular interparliamentary contacts. The article then explores structural and individual determinants of these patterns. The findings are relevant for the larger literature on parliamentary participation, as well as on interparliamentary cooperation in general.